Quantum leaps - Bernstein, Jeremy, 1929- (Belknap Press of Harvard University Press, 2009)
How-- and how pervasively-- quantum mechanics has entered the general culture is the subject of this book, an engaging, eclectic, and thought-provoking look at the curious, boundlessly fertile intersection of scientific thought and everyday life.